ANALISIS KONSEP PEMIKIRAN KI HAJAR DEWANTARA DALAM PERSPEKTIF PENDIDIKAN KARAKTER - Sukri Sukri; Trisakti Handayani; Agus Tinus (Jurnal Civic Hukum, 2016)
Education is a tool to educated nation children who can bring them to enlightenment in totally, education has a purpose to put a nation buildings up that adhere with values of intelligence, sensitivity, and care to nation and country. This research expected can reconstruct national education on crisis set off the problem morality Indonesian nation, rebuild education thought. Ki Hajar Dewantara has purpose of giving answer on morality crisis, that cannot beable to stem the problem of the morality series contemporary Indonesian nation, so education comes back to the prominent in human building that has good individuality (character humans), like the education that has been aspiration by national education sire (Ki Hajar Dewantara). This research has the purpose of knowing some problems in the research focus of research object such as: (1) analyze or inspect the concept thought of education by Ki HajarDewantara. (2) Relevance the idea thought of education by Ki Hajar Dewantara with education character and this research using qualitative research method, whereas the method used in this research is Library Research. The aggregation of data did with investigation way to Ki Hajar Dewantara opuses, especially education and the concept of education idea. Whereas data analysis that used in this research is discourse analysis will reveal various literature from research object. The results of this research show that 1). The concept of education thought by Ki Hajar Dewantara is about humanist education based on independence, external and internal freedom that if you take the red yarn is education that human being or education that can form good students characters. First characteristic is a brilliant mind. Second, intelligent and skill. Third, health of body and spirit. Fourth, pious to the god. 2) The relevance of education concept thought by Ki Hajar Dewantara with education character that both want the same education able to make a form of the whole human, it is freedom human and goodpersonality. This output research expected can give solution or contribution of thought in reconstruct national education for education purpose in building Indonesian character people like education that has been a concept by Ki Hajar Dewantara.